Edukasi dan Pencegahan Hipertensi pada Lansia di Panti Wredha Widhi Asih Surakarta - Gracesya Sherly Euodia Sari; Eleonora Febi Audystia; Fabio Christ Yerdiano; Tasya Wulandari; Othniel Jevon Wibowo; Lilik Ariyanti (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Hypertension, or high blood pressure, is a chronic condition characterized by persistently elevated pressure within the arterial walls. The prevalence of hypertension among older adults continues to increase as life expectancy rises, highlighting the need for sustained preventive and health promotion efforts. This community service program aimed to improve the knowledge and awareness of elderly residents at Widhi Asih Nursing Home, Surakarta, regarding hypertension prevention and management. The intervention included baseline blood pressure screening, elderly exercise sessions, interactive health education based on the "CERDIK" healthy lifestyle approach, and post-intervention blood pressure assessment. The results demonstrated improved participants’ understanding of hypertension risk factors, symptoms, prevention, and management. Data analysis also revealed a significant positive relationship between age and hypertension severity, indicating that advancing age is associated with a higher risk of severe hypertension. The program encouraged older adults to adopt healthy lifestyles independently, thereby enhancing their quality of life, maintaining physical fitness, and reducing the risk of hypertension-related complications.